Intergenerational Mobility of Immigrants in 15 Destination Countries - Leah Platt Boustan; Mathias Fjællegaard Jensen; Ran Abramitzky; Elisa Jácome; Alan Manning; Santiago Perez; Analysia Watley; Adrian Adermon; Jaime Arellano-Bover; Olof Aslund; Marie Connolly; Nathan Deutscher; et al. (Institute of Labor Economics (IZA), 2025)
We estimate intergenerational mobility of immigrants and their children in fifteen receiving countries. We document large income gaps for first-generation immigrants that diminish in the second generation. Around half of the second-generation gap can be explained by differences in parental income, with the remainder due to differential rates of absolute mobility. The daughters of immigrants enjoy higher absolute mobility than daughters of locals in most destinations, while immigrant sons primarily enjoy this advantage in countries with long histories of immigration. Cross-country differences in absolute mobility are not driven by parental country-of-origin, but instead by destination labor markets and immigration policy.
Keywords: J15; J61; J62; 330; immigration; intergenerational mobility